2014
DOI: 10.1158/0008-5472.can-13-2820
|View full text |Cite
|
Sign up to set email alerts
|

Increased Dietary Vitamin D Suppresses MAPK Signaling, Colitis, and Colon Cancer

Abstract: Epidemiologic studies associate low serum vitamin D levels with an increased risk of colon cancer and inflammatory diseases such as inflammatory bowel disease (IBD). 129-Smad3tm1Par/J (Smad3−/−) mice are a model of bacterial-driven colitis and colon cancer when infected with Helicobacter bilis. Thus, we used this mouse model to determine whether increased dietary vitamin D would reduce inflammation and colon cancer. Smad3−/− mice were fed purified diet with either maintenance (1 IU vitamin D/g diet; maintenanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 45 publications
(66 reference statements)
1
80
0
Order By: Relevance
“…The decrease was accompanied with decreased inflammatory cell infiltrates and a reduced expression of proinflammatory cytokines. However, no change in p38 MAPK in colonic epithelial cells was observed in these mice (36).…”
Section: Il6mentioning
confidence: 68%
See 1 more Smart Citation
“…The decrease was accompanied with decreased inflammatory cell infiltrates and a reduced expression of proinflammatory cytokines. However, no change in p38 MAPK in colonic epithelial cells was observed in these mice (36).…”
Section: Il6mentioning
confidence: 68%
“…Calcitriol also increases the expression of the inhibitor of NF-kB, IkB (32,33,35). These effects of calcitriol on NF-kB have also been shown in a mouse model of colon cancer where an increase in dietary vitamin D resulted in a 4.5-fold decrease in NFkB activation in colonic epithelial cells (36). Furthermore, colon cancer cells treated with a vitamin D-receptor antagonist showed increased NF-kB activity and reduced IkB expression (37).…”
Section: Cancer Epidemiol Biomarkers Prev; 24(12) December 2015mentioning
confidence: 72%
“…Further, numerous experimental Helicobacter sp. infections in mice have reproduced salient features of IBD and hepatobiliary disease observed in marmosets (Erdman et al, 2009;Fox, 2002;Fox et al, 1996Fox et al, , 2011Hailey et al, 1998;Knutson et al, 2013;Maggio-Price et al, 2005;Mangerich et al, 2012;Meeker et al, 2014).…”
Section: Discussionmentioning
confidence: 87%
“…A suppressed production of inflammatory cytokines, such as interleukin (IL)-1, IL-6, IL-8, IL-17, and TNF-␣ is consistently demonstrated in in vitro and in vivo cancer models (5,162,240,330) (FIGURE 7). In a preclinical SMAD3 knockout model of colitis and colon cancer, Meeker et al (304) showed that a high vitamin D diet decreases NF-B activation in colonic epithelial cells, which is reflected by decreased inflammatory cell infiltrates and reduced expression of proinflammatory cytokines during initiation of carcinogenesis (304). In line with this, a strong inverse association is found between 25(OH)D status and the risk of colorectal cancer with high-level lymphocytic reactions which suggests a role for vitamin D in cancer immunoprevention through modulation of the host-tumor interaction (419).…”
Section: D) Effects On Inflammation In Cancermentioning
confidence: 99%